Pengembangan Instrumen Tes Geometri Berbasis Tangram untuk Mengukur Kemampuan Berpikir Kreatif Siswa Sekolah Dasar - Kusnul Khotimah; Juwaedi Juwaedi (MASALIQ, 2026)
Although the assessment of mathematical creativity has received increasing attention in various studies, the development of a tangram-based geometry instrument to measure elementary school students’ creative thinking ability remains limited. This study aims to develop a valid and practical tangram-based geometry test instrument for fourth-grade students and to describe the creativity profile based on Van Hiele’s levels of geometric thinking. This study employed a mixed-methods approach with the 4-D Research and Development (R&D) model, namely Define, Design, Develop, and Disseminate, involving 30 students selected through purposive sampling. Data were collected using Student Worksheets in the form of open-ended questions covering the indicators of fluency, flexibility, originality, and elaboration, and were then analyzed through expert validation, practicality assessment, descriptive statistics, and the qualitative model of Miles and Huberman. The results showed that the instrument obtained an average expert validation score of 4.43 and a teacher practicality level of 85%. A total of 43.33% of the students were categorized as creative, with the highest achievement on the fluency indicator. Students at Van Hiele Level 1 showed a very creative profile, whereas students at Level 0 tended to show cognitive rigidity due to dependence on static visual prototypes. These findings contribute to the development of the theory of mathematical creativity assessment and show that the tangram-based geometry instrument is feasible for use in supporting formative evaluation. This study underscores the importance of integrating manipulative-based open-ended tasks in geometry learning and opens opportunities for further research on broader populations and grade levels.